Bringing Language Diversity Into Integrity Research—What, Why, and How. Issue 1 (2nd January 2022) - Murphy, Greer A.
Abstract: This article reviews three decades of scholarship to establish connection(s) between language diversity and integrity research. It makes the case that by shifting the vocabulary, methods, and scope of our work, we scholar-practitioners and integrity professionals become better able to equitably support multilingual learners in their writing from sources and avoiding unintentional plagiarism. It makes the case that doing so is more than a desirable goal—it is an achievable one.